1999
DOI: 10.1086/311990
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Density Distribution of Virialized Cold Dark Matter Halos

Abstract: An analytic collapse model for the formation and density distribution of virialized cold dark matter halos is proposed. Hierarchical structure formation is taken into account explicitly. Monte Carlo methods are used to generate samples of mass histories of virialized halos. The mean density distribution found from the collapse model is in good agreement with numerical results in the mass range from 10 11 M ⊙ to 10 15 M ⊙ and in the radial range form 0.05r 200 to r 200 .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…Some attempts to incorporate tangential velocities within the framework of spherical symmetry have also been made by [9,65,122]. Along this line, one may also refer to work by [40,63,89,91] and references therein.…”
Section: Previous Analytical Models For Halo Formation: the Sphericalmentioning
confidence: 99%
See 1 more Smart Citation
“…Some attempts to incorporate tangential velocities within the framework of spherical symmetry have also been made by [9,65,122]. Along this line, one may also refer to work by [40,63,89,91] and references therein.…”
Section: Previous Analytical Models For Halo Formation: the Sphericalmentioning
confidence: 99%
“…The projected surface density is given by where ξ is the projected distance from the center of the halo, and z = (r 2 − ξ 2 ) 1/2 . For the TIS, we substitute equation (61) in equation (89), and get [68,106]. For spherically symmetric lenses, one important quantity is the interior mass M (ξ) inside a cylinder of projected radius ξ centered around the center of the lens.…”
Section: The Interior Mass Profilementioning
confidence: 99%
“…Studies based on analytical and seminumerical methods also have shown that eq. (1) is a good approximation for the density profiles of typical equilibrium cold dark matter haloes (e.g., Syer & White 1998; Avila-Reese, Firmani, & Hernández 1998;Salvador-Solé, Manrique & Solanes 1998;Raig, González-Casado & Salvador-Solé 1998;Henriksen & Widrow 1999;Nusser & Sheth 1998;Kull 1999;Lokas 1999). Nevertheless, the applicability of the NFW profile has some limits.…”
Section: Introductionmentioning
confidence: 99%
“…There are good reasons for this: LSB galaxies are dark matter dominated down to small radii, making the inference of their dark matter properties much less sensitive to the stellar mass than in higher surface brightness spirals. In the most straightforward analyses, the data appear to contradict a basic prediction of the ΛCDM structure formation scenario, that dark matter halos should have cusps at small radii (a density distribution ρ ∼ r −γ with γ ≈ 1: Dubinski 1994;Cole & Lacey 1996;Navarro, Frenk, & White 1997 (hereafter NFW); Tormen, Bouchet, & White 1997;Moore et al 1998Moore et al , 1999bTissera & Dominguez-Tenreiro 1998;Nusser & Sheth 1998;Syer & White 1998;Avila-Reese, Firmiani, & Hernandez 1998;Salvador-Śole, Solanes, & Manrique 1998;Jing 2000;Jing & Suto 2000;Kull 1999;Klypin et al 2001;Ricotti 2003;Power et al 2003;Diemand et al 2005). The data are apparently more consistent with a nearly constant density core (γ ≈ 0).…”
mentioning
confidence: 97%